2006
DOI: 10.1089/jam.2006.19.510
|View full text |Cite
|
Sign up to set email alerts
|

Validity ofIn VitroTests on Aqueous Spray Pumps as Surrogates for Nasal Deposition, Absorption, and Biologic Response

Abstract: This research investigated the impact of the full range of in vitro spray characterization tests described in the FDA Draft Bioequivalence Guidance on nasal deposition pattern, pharmacokinetics, and biological response to nicotine administered by two aqueous nasal spray pumps in human volunteers. Nicotine was selected as a model drug (even though it is not locally acting) based on its ability to alter cardiac function and available plasma assay. Significant differences in pump performance-including mean volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 15 publications
0
81
0
Order By: Relevance
“…(52) The choice of 1 m/s spray velocity was determined based on an earlier report by Frank et al (8) that showed higher nasal spray penetration at 1 m/s compared to 3 m/s and 10 m/s.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…(52) The choice of 1 m/s spray velocity was determined based on an earlier report by Frank et al (8) that showed higher nasal spray penetration at 1 m/s compared to 3 m/s and 10 m/s.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Materials penetrating the nasal valve available for deposition in the turbinate region are desirable. Both gamma scintigraphic measurements in human volunteers and nasal airway replicas have been used to study the deposition pattern of nasal delivery (62)(63)(64)(65)(66)(67). These studies identify several key parameters including plume angle, droplet size, plume velocity, and inspiratory flow rate that may influence the deposition pattern of nasal spray devices.…”
Section: Nasal Spraymentioning
confidence: 99%
“…The delivery performance of any aerosolized droplets introduced via the nasal cavity depends on many factors, such as the design of the pump, the physical properties of the formulation, and the position of administration. (21)(22)(23)(24)(25) In this present work, we have examined the effects of PBS versus sodium chloride (NaCl) diluents on stability and potency of NE-based vaccines when stored at room temperature (accelerated conditions). We have also evaluated the ability to deliver NE-based vaccines using standard nasal spray devices.…”
Section: Introductionmentioning
confidence: 99%